2019
DOI: 10.1155/2019/6407098
|View full text |Cite
|
Sign up to set email alerts
|

Do Systemic Factors Influence the Fate of Nonunions to Become Atrophic? A Retrospective Analysis of 162 Cases

Abstract: Introduction. Nonunions are a challenge for orthopedic surgeons. In hypertrophic nonunions, improvement of mechanical stability usually is the satisfactory treatment, whereas in atrophic nonunions improvement of the biological environment is most important. However, scientific evidence revealed that “avital” nonunions are not avascular and fibrous tissue contains cells with osteogenic potential. To find out if systemic factors suppress this intrinsic potential in atrophic nonunions, this study compares charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Furthermore, proteomic analysis of serum showed that complement C6, C3 and C4, which their strongly activating phenotype is less favourable for MSC-related immunosuppression 85 , were up-regulated in the serum of NU patients compared to healthy controls 101 . Altogether, the systemic changes of various serum mediators could explain the lower proliferative and osteogenic potential as well as the altered immunomodulatory potential of the MSC pool in BM that we noted in our study and by others for NU fracture patients 103 .…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, proteomic analysis of serum showed that complement C6, C3 and C4, which their strongly activating phenotype is less favourable for MSC-related immunosuppression 85 , were up-regulated in the serum of NU patients compared to healthy controls 101 . Altogether, the systemic changes of various serum mediators could explain the lower proliferative and osteogenic potential as well as the altered immunomodulatory potential of the MSC pool in BM that we noted in our study and by others for NU fracture patients 103 .…”
Section: Discussionsupporting
confidence: 67%
“…While the pool of BMSCs in nonunion patients was decreased compared to healthy subjects, we inferred that the NCs were the BMSCs in nonunion patients. In atrophic nonunion, it is also an important factor to improve the biological environment [36]. The purpose of using bone morphogenetic proteins is stimulating osteogenic activity at the nonunion site [37].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies analysing differences in fracture healing between male and female fracture patients are rather rare and results are di cult to interpret, because other in uencing factors, including fracture type, degree of tissue trauma, body weight and clinical manifestation of osteoporosis, frequently differ between men and women. It was shown for some types of fractures that male patients displayed more rapid fracture healing and women had an increased risk for atrophic non-unions rather than hypertrophic non-unions in males [14,15]. One clinical study reported signi cantly increased blood levels of the Wnt/βcatenin-signalling inhibitor Sclerostin in male geriatric hip fracture patients compared to female agematched patients, whereas the concentrations of another Wnt/β-catenin-signalling inhibitor, Dickkopf-1 were reduced [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that sex hormones like oestrogen have considerable effects on bone healing [11][12][13]. There are also clinical indications that male patients display more rapid fracture healing and that women may have an increased risk for atrophic non-unions rather than hypertrophic non-unions as observed in males [14,15]. By contrast, there are also clinical studies reporting no in uence of sex on fracture healing in speci c fracture types [16][17][18].…”
Section: Introductionmentioning
confidence: 99%